American International Relations and the academia in the Global South - Vallejo, María Fe (El Outsider: Journal of International Relations and Political Science, 2022)
In 1977, Stanley Hoffman affirmed that International Relations Theory was consolidated as an American discipline, not only because of the rise of the United States as a global power, but because of the epistemological and ontological foundations on which it was grounded. However, the heritage of the American academy supposes a series of implications for the study of international relations in the Global South, where it is worth questioning whether replicating it allows us to understand the complexities of colonialism, imperialism, racism, culture and gender issues that have permeated the discipline. Therefore, this article seeks to understand the implications of reproducing the academic patterns of American International Relations in the Global South; affirming that the homogenization of the discipline reproduces an ethnocentric logic that has relegated certain voices to the margins of the discipline.
Keywords: International Relations Theory; Ethnocentrism; Non-Western; Epistemology